A MIDDLE HOLOCENE STRESS CHANGE IN THE UDOKAN RANGE VOLCANIC ZONE, EASTERN SIBERIA - Rasskazov S.V. (My University, 1999)
During the last 12 thousand years the Udokan volcan oes erupted alkaline basalts and trachites. The strike of the fissure magma channels changed fr om NW to NE during the Middle Holocene in the interval of 7.9-4.6 thousand years ago. The Udokan volcanic activity was controlled by the structures of the northeastern segment of the Baika l Rift and of the western segment of the Olekma-Stanovoi Orogenic Belt. It is suggested that the outbreak of the young volcanism was associated with an impulse of NW compression in the upper crust of the Olekma-Stanovoi Belt, and that the attenuation of the volcanic activity o ccurred as the compression relaxed and changed to a dominant NW crustal extension, the stress patt ern typical of the Baikal Rift.
Keywords: Holocene; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен